Development of a climatic map of attenuation by rainfall for Turkiye - (:unkn) unknown (IEEE, Piscataway, NJ, United States, 1994)
In this work, a climatic map of rainfall attenuation for TURKIYE is developed to be produced. For this purpose, the meteorological data with 24 hour integration time for 214 sites throughout TURKIYE is gathered and processed to obtain 1-5 minute data base. In the second stage, the attenuation is predicted by the Leitao-Watson Model. In the final stage the regional and global attenuation maps are prepared by countouring procedure, depending on exceedance probabilities, frequency, polarisation and satellite position.